On Morphology and Morphometry of Trichuris ovis Abildgaard, 1795 Recovered from Ruminants of Ladakh, India - Kuchai, Javid Ahmad; Ahmad, Fayaz; Chishti, Mohammad Zahoor; Dar, Javid Ahmad; Tak, Hidayatullah (Journal of Buffalo Science, 2013)
Morphology and morphometry is used as tools for parasite identification since times immemorial, however this trend has been no longer used since the last decades and the identification became dependent on molecular characterization. However, this is possible in developed Countries while as the developing and underdeveloped Countries, like India, still largely depend on the traditional techniques. In this investigation an attempt was made to study the morphology and morphometry of adult Trichuris ovis recovered from caecum of the ruminants in Ladakh in order to access the effect of the study area, host, intensity, age, sex of the host and methodology on morphology of the parasite. It has been found that all these factors pose a little effect on the parasite identification were of minor importance because they were found within the range of similarity and were not good enough to label it as a new species as was expected. However, some descriptive features might be helpful in the parasite identification.